Medical complications of pregnancy - Angel Müller, Edith (2015)
Urinary infection and pregnancy. Malaria in pregnancy. Dengue in pregnancy. Obesity and pregnancy: Pathophysiology and complications. Perinatal outcome of obesity in pregnancy. Hyperprolactinemia and thyroid disorders during pregnancy. Hyperthyroidism and pregnancy.